(untitled) (Research, Society and Development, 2022)
Objective: To characterize nurses’ knowledge about the risk and prevention of corneal injury in the adult ICU. Methods: Qualitative study, developed through an integrative review. Inclusion criteria were: articles published from 2014 to 2019, in Portuguese and English, available online in full in the proposed databases. Results: There was a lack of knowledge on the subject in question, basing its rhetoric on personal experiences and with low scientific content. Conclusion: There is a difficulty based on clarification and understanding on the part of nurses regarding the risks and prevention related to corneal injury. This reality demonstrates the relevance of investments in updates on the proposed topic aimed at the professional category of nurses.